Issues in implementing affirmative action in Malaysia - Mohd Anuar, Haslinda; Abdul Wahab, Harlida; Mohamed, Mazita; Azhar, Alias (Global Academic Excellence, 2018)
Equality is equity. In other words, equality can be associated with being equal in status, rights or opportunities. Article 8 (1) and (2) of the Malaysian Federal Constitution address the concept of equality in Malaysia. However, the equality provision in Article 8(1) is not absolute. This can be seen, for example, under Article 136 of the Federal Constitution which requires all federal employees shall be treated impartially regardless of their races. However, it is important to note that Article 153 of the Federal Constitution did provide special privileges, quotas and reservations for Malays and the natives of Sabah and Sarawak, and this provision has been challenged legally and politically. The late Tun Suffian managed to reduce the gap between Articles 136 and 153 by introducing the concept of ‘affirmative action’ whereby the reservations and quotas are permissible under the Federal Constitution. The objective of this paper is to identify the issues in implementing affirmative action in Malaysia. Doctrinal legal research methodology has been used to achieve the objective. It was found that there are many issues have been posed on the implementation of affirmative action and the sustainability of the concept is another challenge yet to be determined.